ANTIMALARIAL COMPOUNDS FROM ENDOPHYTIC FUNGI OF BROTOWALI (Tinaspora crispa L) - Elfita Elfita; Muharni Muharni; Munawar Munawar; Leni Legasari; Darwati Darwati (Universitas Gadjah Mada, 2011)
The term endophytic refers to a bacteria or a fungi microorganism that colonizes interior organs of plants, but does not have pathogenic effects on its host. In their symbiotic association, the host plant protects and feeds the endophytic, which